PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN DESENTRALISASI DAN KARAKTERISTIK SISTEM INFORMASI AKUNTANSI MANAJEMEN SEBAGAI VARIABEL MODERATING - MURTANTO MURTANTO; WINDA ARUM HAPSARI (Jurnal Bisnis dan Akuntansi, 2006)
The relationship between budget participation and managerial performance has been examined in several accounting studies with conflicting results. The conflicting evidence may reflect the influence of a contingent variable. This study examined the influence of decentralizetion and management accountting system information characteristics as moderating variable in the relationship between budget participation and managerial performance. Personally administered questionnaires is conducted to collect data that is distributed to 150 functional managers on manufacturing and service companies in jakarta and Tangerang, but only 100 questionnaires were analyzed. The sample method is convenience. While, this study use multiple regression model as the technical analysis. Based on respons of 100 managers in Jakarta and Tangerang, the result of study shows that the interaction between budget participation with decentralizetion and interaction between budget participation with management accounting system information characteristics significantly influence to managerial performance. Although interaction between budget participation with decentralization and management accounting system information characteristics significantly influence to managerial performance, both of them has opposite relation with managerial performance, since .their regression coefficients are negative. It means that, at high level of decentralization, the effect of budget participation on managerial performance will be low, and vice versa. At high willingness of management accounting system information characteristics, the effect of budget participation on managerial performance will be low, and vice versa.